Quantum theory of near-field electrodynamics - Keller, Ole; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
Quantum Theory of Near-field Electrodynamics gives a self-contained account of the fundamental theory of field-matter interaction on a subwavelength scale. The quantum physical behavior of matter (atoms and mesoscopic media) in both classical and quantum fields is treated. The role of local-field effects and nonlocal electrodynamics, and the tight links to the theory of spatial photon localization are emphasized. The book may serve as a reference work in the field, and is of general interest for physicists working in quantum optics, mesoscopic electrodynamics and physical optics. The macroscopic and microscopic classical theories form a good starting point for the quantum approach, and these theories are presented in a manner appropriate for graduate students entering near-field optics.
Introduction -- Part A: Microscopic Classical Theory -- Part B: Macroscopic Classical Theory -- Part C: Quantum Theory with Classical Fields -- Part D: Quantum Electrodynamic Theory.
Electronic reproduction.
Keywords: Electrodynamics; Quantum Theory; Electronic books